2003
DOI: 10.1063/1.1606105
|View full text |Cite|
|
Sign up to set email alerts
|

Electron-beam-induced segregation in InGaN/GaN multiple-quantum wells

Abstract: Articles you may be interested inLow energy electron beam induced damage on InGaN/GaN quantum well structure J. Appl. Phys. 109, 083105 (2011); 10.1063/1.3574655 Indium redistribution in an InGaN quantum well induced by electron-beam irradiation in a transmission electron microscope Appl. Electron-beam-induced strain within InGaN quantum wells: False indium "cluster" detection in the transmission electron microscope Appl. Phys. Lett. 83, 5419 (2003); 10.1063/1.1636534 Investigation of V-Defects and embedded in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 16 publications
0
43
0
Order By: Relevance
“…However, as the electron dose increased, indium-rich clusters formed, just as in the Cambridge grown samples [18]. O'Neill et al [19] also reported that In-rich clusters formed as a result of electron beam damage in their specimens. We also prepared TEM specimens using only mechanical polishing instead of using a combination of mechanical polishing followed by ion beam thinning.…”
Section: Transmission Electron Microscopymentioning
confidence: 97%
“…However, as the electron dose increased, indium-rich clusters formed, just as in the Cambridge grown samples [18]. O'Neill et al [19] also reported that In-rich clusters formed as a result of electron beam damage in their specimens. We also prepared TEM specimens using only mechanical polishing instead of using a combination of mechanical polishing followed by ion beam thinning.…”
Section: Transmission Electron Microscopymentioning
confidence: 97%
“…InGaN materials tend to degrade during post processing and characterization by the most direct technique, electron-beam microscopy [67,86]. And less direct techniques, such as cathodoluminescence, have been unable to unambiguously determine the spatial distribution of indium.…”
Section: Compositional Inhomogeneitiesmentioning
confidence: 99%
“…The homogeneity of InN-GaN alloys is widely debated 7,8 and the existence of a miscibility gap is postulated that limits the indium solubility in GaN leading to a local formation of In-rich nanoclusters. Concerns were recently raised 9,10 and debated 11 about the use of electron microscopy to investigate the non-equilibrium state of the InGaN system since the exposure of specimens to high-energy electron beams may enhance phase separation.…”
Section: Introductionmentioning
confidence: 99%